2019
DOI: 10.1371/journal.pone.0210149
|View full text |Cite
|
Sign up to set email alerts
|

Educational attainment predicts negative perceptions women have of their own climate change knowledge

Abstract: Education may encourage personal and collective responses to climate change, but climate education has proven surprisingly difficult and complex. Self-perception of knowledge and intelligence represent one factor that may impact willingness to learn about climate change. We explored this possibility with a case study in Raleigh, North Carolina in 2015 (n = 200). Our goal was to test how gender and ethnicity influenced perceptions people had of their own climate change knowledge. Survey respondents were asked h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 59 publications
1
15
1
Order By: Relevance
“…1). A previous study showed that women's self-perceived knowledge is higher than men's among people with low levels of education but higher for men among people with high levels of education [93]. It should be noted, however, that our study had some gender imbalances, so we should be cautious when interpreting the interaction between gender and education results.…”
Section: Risk Perceptionsmentioning
confidence: 71%
“…1). A previous study showed that women's self-perceived knowledge is higher than men's among people with low levels of education but higher for men among people with high levels of education [93]. It should be noted, however, that our study had some gender imbalances, so we should be cautious when interpreting the interaction between gender and education results.…”
Section: Risk Perceptionsmentioning
confidence: 71%
“…1). A previous study showed that women's self-perceived knowledge is higher than men's among people with low levels of education but higher for men among people with high levels of education [98]. It should be noted, however, that our study had some gender imbalances, so we should be cautious when interpreting the interaction between gender and education results.…”
Section: Educational Attainmentmentioning
confidence: 71%
“…The In a study (Selm et al, 2019) during data collection, participants were asked how strongly they agreed with the phrase "I feel familiar with climate change" with a sample of young people, most of whom have a university qualification, at 49.2% of the total sample in Raleigh, North Carolina. a positive correlation was observed between education and gender, where women's self-perceived knowledge was higher than men among people with low levels of educational achievement, while highly educated men had a higher self-perception of climate change knowledge than less educated men women were almost one point higher than men on the self-reported climate change knowledge scale at the lowest level of achievement And about 0.6 points less than men at the highest level of educational attainment.…”
Section: Climatementioning
confidence: 99%